2018
DOI: 10.1002/celc.201800013
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Incorporation Strategy for Bimetallic FeCo‐Doped Carbon as Highly Efficient Bifunctional Oxygen Electrocatalysts

Abstract: Highly efficient bifunctional oxygen reduction reaction/oxygen evolution reaction (ORR/OER) electrocatalysts are of great significance for developing rechargeable metal–air batteries. A facile in situ incorporation strategy was proposed to introduce an iron‐based complex into a cobalt‐based ZIF‐67 framework. The resultant FeCo−N/C exhibited an excellent ORR activity with a high half‐wave potential of 0.84 V and simultaneous outstanding OER activity with a low overpotential of 370 mV at a current density of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…To replace these expensive noble catalysts, low cost alternatives such as transition metal oxides have been considered . Among them, cobalt‐based oxides are envisaged as the most active catalysts for the electrocatalysis of oxygen . Spinel‐type Co 3 O 4 nanoparticles have received a great deal of attention as bifunctional materials for oxygen reactions due to their higher intrinsic activity (compared to noble metals) and suitable stability, in particular for the OER .…”
Section: Introductionmentioning
confidence: 99%
“…To replace these expensive noble catalysts, low cost alternatives such as transition metal oxides have been considered . Among them, cobalt‐based oxides are envisaged as the most active catalysts for the electrocatalysis of oxygen . Spinel‐type Co 3 O 4 nanoparticles have received a great deal of attention as bifunctional materials for oxygen reactions due to their higher intrinsic activity (compared to noble metals) and suitable stability, in particular for the OER .…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging that the performance of these catalysts is at par with or even superior to that of commercial IrO 2 ‐Ni (η 10 =240 mV, Tafel slope=119.1 mV dec −1 ). Meanwhile, the OER activity of these samples are also better than the previous reported earth abundant transition metal phosphide and sulfide as shown in Figure S4a and table S1, e. g. Ni x B (η 10 =380 mV), N,S‐CNT (η 10 =330 mV), NiS/Ni foam (η 10 =335 mV), Co−P (η 10 =345 mV), FeCo−N/C (η 10 =370 mV), FeCoNi (η 10 =400 mV), Fe‐CoP/Ti (η 10 =230 mV), NiCoP (η 10 =280 mV), CP/CTs/Co−S (η 10 =280 mV), CoSe 2 (η 10 =430 mV), Co 5.47 N NP@N‐PC (η 10 =248 mV) . Moreover, satisfied durability of Ni−B−O@NiB 2 as an OER catalytic electrode has been confirmed as little decay of its activity was observed according to the polarization curves after 500 cycles (Figure d).…”
Section: Resultsmentioning
confidence: 61%
“…In Ru 3p spectrum, the peaks at 461.8 and 483.9 eV are attributed to the Ru 3p 3/2 and Ru 3p 1/2 of metallic Ru (0), indicating that Ru clusters are dispersed in carbon matrix. In addition, high‐resolution N 1s spectrum of Ru‐CN/MC can be deconvoluted into two peaks at 397.0 and 398.5 eV, which can be assigned to metal‐N coordination and pyridinic N, respectively . Combined with the results obtained from elemental mapping, it can be concluded that the nitrogen from melamine was incorporated in carbon support and contributed to form Ru clusters embedded in nitrogen‐containing carbon matrix.…”
Section: Resultsmentioning
confidence: 78%
“…In addition, highresolution N 1s spectrum of Ru-CN/MC can be deconvoluted into two peaks at 397.0 and 398.5 eV, which can be assigned to metal-N coordination and pyridinic N, respectively. [58][59] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 be concluded that the nitrogen from melamine was incorporated in carbon support and contributed to form Ru clusters embedded in nitrogen-containing carbon matrix.…”
Section: Resultsmentioning
confidence: 99%